The Santorini 2024–2025 Volcano‐Tectonic Sequence: Constraining the Initial Phase of the Intra‐Caldera Unrest - C. Papazachos; M. Foumelis; S. Bitharis; Ch. Pikridas; E. Trasatti; E. Papageorgiou; Ch. Ventouzi; Ch. Kkallas; G. Vougioukalakis; O. Vaselli (Geophysical Research Letters, 2025)
Abstract After less than 14 years from the previous 2011–2012 unrest, the Santorini volcano entered a new unrest phase, involving intra‐caldera deformation since July 2024 and microseismicity mainly after mid‐September 2024. We examine the first phase of this unrest, identified by GNSS and Synthetic Aperture Radar Interferometry data as an almost radial expansion of the northern caldera by ∼7 cm within 6 months (7/2024–12/2024). The unrest also involves a seismic swarm along an 8 km × 6 km segment of the Kameni line fault, with events up to ML3.8. We model the inflation with a near‐vertical spheroid at a depth of ∼3.4 km, resulting in a 6+ million m3 expansion within 6 months. While the proposed deformation source is almost identical for the two unrests, which also show similar seismicity and deformation trends, we do not observe the significant increase of H2 emissions associated with the 2011–2012 unrest.